Cultivation of multidisciplinary professional talent for the internationalization of China's Agri-Sci-tech industry - Xiong Xin (Social Sciences and Humanities Open, 2025)
This research explores the challenges and opportunities associated with cultivating multidisciplinary talent for the internationalization of China's agricultural science and technology (Agri-Sci-Tech) industry. Agriculture serves as the cornerstone of China's national economy, and industry internationalization is critical to global agricultural development. However, China faces significant challenges, including insufficient international perspective among professionals, shortages in international cooperation experience, obstacles in the international public opinion environment, and inadequate professional knowledge among translators. Addressing these issues will enable China to integrate into the global agricultural value chain and enhance its international competitiveness.The study employs a mixed-methods approach, integrating a literature review, comparative analysis, and case studies.The necessity for composite talent with both professional expertise and foreign language proficiency is highlighted. This study proposes strategies such as cultivating “professional + foreign languages” and “foreign languages + professional” talent, leveraging translation technology, and developing specialized textbooks and communication platforms. These initiatives aim to strengthen China's global competitiveness and facilitate international agricultural collaboration.